Pendampingan Perumusan Rencana Strategis (RENSTRA) di Sekolah Dasar Negeri 002 Pantai Cermin Pekanbaru - Ansori, Ahmad; Irawati, Irawati; Hasri, Salfen; Setyaningsih, Rini; Al Ghifari, Mahdini (EL-EMIR INSTITUTE, 2024)
A strategic plan is a crucial foundation for an organization in charting steps toward organizational success. Therefore, the formulation of an appropriate strategic plan is essential. This community service was conducted at SDN 002 Pantai Cermin Pekanbaru, involving all human resources at the school. The objective of this community service was to provide assistance in formulating the Human Resource (HR) Strategic Plan at SDN 002 Pantai Cermin Pekanbaru. The methods employed in this activity included observation through pre-tests, lectures delivered via PowerPoint presentations, practical training sessions, and evaluation through post-tests. The results of the community service indicated that: the human resources at SDN 002 Pantai Cermin Pekanbaru successfully formulated a realistic and implementable vision, mission, and strategic objectives; they were able to develop a detailed implementation and monitoring plan applicable in both the short and long term; and participants expressed high satisfaction with the community service activities.